Fenomena Fanatisme Suporter Sepak Bola Dan Dampaknya Terhadap Interaksi Sosial Masyarakat - Tegar Wicaksana Sutisna; Abdul Lukuta; Moh Vikri Manorek; Djafar Basiha; Ariyanto Kasim; Meri Haryani; Khoirul Anwar Pulungan; Hartono Hadjarati; Safri Irawan (Universitas Negeri Gorontalo, 2026)
Football supporter fanaticism is a social phenomenon arising from strong emotional attachment and loyalty to a club. This study aims to examine the factors influencing supporter fanaticism and its impact on social life. A qualitative literature review was conducted using scientific articles published between 2016 and 2026. The collected data were analyzed descriptively to identify key patterns and findings. The results indicate that social identity, group loyalty, and community influence are the main factors shaping fanatic behavior among supporters. Fanaticism contributes positively by strengthening solidarity, social cohesion, and a sense of belonging. However, it may also lead to conflict, aggressive behavior, and provocative interactions on social media. These findings highlight the multifaceted nature of football supporter fanaticism. Therefore, promoting sportsmanship values and digital literacy is essential to enhance its positive contributions while minimizing its negative consequences in society.